(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In article considerate how was the training of leaderships in history during in time Aleksandr Makedonskiy, Temuchin, Amir Temur, then later considerate experience of Russian emperor Petr I. The Training System of sergeants armed forces USA, German and their classification, the training system of sergeants armed forces Kazahstan and information of their training centers. Making compare between systems of training sergeants the armed forces of Uzbekistan, give an account of innovation minds about future developments